Environmental Concern: Antecedents of Ecotourism Visit Intention with Time Perspective and Destination Image as Determination Variables - Yohan Wismantoro; MG Westri Kekalih Susilowati; Amalia Nur Chasanah; Vincent Didiek Wiet Aryanto (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2023)
Environmental damage and sustainability become the center of attention along with climate change today. One of the interesting things is the change in behavior in the consumption of products categorized as